Seismic performance assessment of pile-supported wharves retrofitted by carbon fibre–reinforced polymer composite considering ageing effect. Issue 4 (April 2016) - Banayan-Kermani, Ali; Bargi, Khosrow; Heidary-Torkamani, Hamid
This study aims to assess seismic vulnerability of a typical pile-supported wharf considering ageing effects due to chloride-induced corrosion of the reinforced concrete piles. In order to improve the seismic performance of corroded wharves, carbon fibre–reinforced polymers is used as a retrofit technique. Three-dimensional model of the wharf is constructed using SAP2000, and pushover analysis is conducted to deduce the capacity curve of the wharf and establish quantitative criteria for bound of damage states. Then, using eight ground motion records, nonlinear static analysis called capacity spectrum method is used to evaluate the response of initial ( t  = 0 years), corroded ( t  = 25, 50, 75 years) and carbon fibre–reinforced polymer-retrofitted-corroded ( t  = 50, 50, 75 years) pile-supported wharf structures. In order to assess the seismic vulnerability of wharves quantitatively, fragility curves are developed using two different engineering demand parameters, including displacement ductility factor ( µd ) and state of plastic hinges. These fragility curves demonstrate the evolving damage potential under different levels of intensities taking into account time-dependent corrosion-induced deterioration. In addition, these curves reveal the effectiveness of carbon fibre–reinforced polymer method on the fragility reduction. Results indicate an increment in seismic vulnerability throughout the lifetime of the structure due to corrosion denoting the considerable impact of deterioration due to ageing effects on structural response. Moreover, using carbon fibre–reinforced polymer jacketing as a retrofit and repair method for corrosion-induced damaged structures can remarkably enhance their seismic performance.